Effect of inhaled morphine on the development of breathlessness during exercise in patients with chronic lung disease. Issue 6 (June 1996) - Leung, R; Hill, P; Burdon, J
Abstract : BACKGROUND: Inhaled morphine has previously been shown to increase exercise endurance in patients with chronic lung disease. A similar study was performed to determine whether inhaled morphine reduces the sensation of breathlessness in this group of patients. METHODS: A randomised double blind study on the effect of nebulised morphine on both exercise induced breathlessness and maximum achievable power output using isotonic saline as a control was performed in 10 patients with stable chronic lung disease. Each subject performed a progressive exercise test (Jones' stage I) on an electrically braked cycle ergometer. The work load was increased by 10 watts per minute and subjects exercised to exhaustion. At the end of each minute of exercise patients were asked to rate their degree of breathlessness according to a modified Borg scale. All subjects were randomised to receive either inhaled morphine sulphate 1 mg/ml (5 ml) or isotonic saline (5 ml) by wet nebulisation. The effect of morphine and saline on the achieved exercise capacity and the development of breathlessness during exercise was tested on separate days. RESULTS: The mean dose of morphine inhaled was 1.24 mg. There was no difference in maximum power output achieved, minute ventilation at maximum power output, nor the degree of breathlessness at maximum power output between the groups treated with morphine and placebo. The degree of breathlessness was related to the power output achieved during exercise by a power function relationship (mean r: morphine = 0.86, saline = 0.87). However, there was a wide variation in the sensation for any given power output in both groups. There was no difference in the group mean slopes (morphine = 1.15, saline = 1.00) or intercepts (morphine = 0.07, saline = 0.15) in this relationship between the morphine and saline treatment groups. CONCLUSIONS: In patients with severe chronic lung disease inhaled morphine in the doses used in this study does not relieve exercise induced breathlessness nor does it increase maximum power output achieved during progressive exercise.